Exploring the scope for advocacy by paediatricians. Issue 6 (1st December 1999) - Rudolf, M C J; Bundle, A; Damman, A; Garner, M; Kaur, V; Khan, M; Robinson, G; Ruge, S; Waterston, T
Abstract : AIMS: To ascertain the type and extent of problems requiring advocacy in paediatrics. To develop an approach for analysing problems according to their root causes and the level of society at which advocacy is needed. METHODS: Nine paediatricians kept detailed clinical diaries for two weeks to identify problems. Classifications were developed to categorise problems by cause and the level of society at which they needed to be addressed. The press was surveyed for one week for childhood issues attracting media attention. RESULTS: 60 problems requiring advocacy were identified. Root causes included failures within agencies, between agencies, and inadequate provision. In addition to advocacy required individually, "political" action was needed at the community level (16 issues), city level (16 issues), and nationally (15 issues). 103 articles were found in the press, these did not relate closely to issues identified by clinicians. CONCLUSIONS: Many opportunities for advocacy arise in the course of daily work. A systematic way of analysing them has been developed for use in planning action. To optimise the health and health care of children, there is a need to train and support paediatricians in advocacy work for local as well as national issues. Ten issues were identified that might be prioritised by paediatricians working on an agenda for action.